Submission of Marital Dispensation for Religious Courts in Central Java: Study of Minimum Pair Age Standards Along With Judge's Attitudes and Wisdomes - Mustofa, Kholifatun Nur (De Jure: Jurnal Hukum dan Syari'ah, 2019)
This paper examines the minimum age limit for filing a marital dispensation focused on the Central Java Religious Courts. This paper examines the judge's policy in the marital dispensation in religious courts in Central Java regarding the marital age limit by using anthropology approach. by reviewing the judges' decisions in the marital dispensation cases focusing on the tendency of the brides' ages to see the minimum age to have marital dispensation in each region. The research shows that the lowest age to file a marital dispensation in Central Java is 12 years 9 months for female, and 15 years 10 months for male. The majority of judges do not consider the age of the parties, but rather the reasons and conditions of the party submitting.Artikel ini membahas batas usia minimum untuk mengajukan dispensasi perkawinan yang berfokus pada Pengadilan Agama Jawa Tengah. Makalah ini membahas kebijakan hakim dalam dispensasi perkawinan di pengadilan agama di Jawa Tengah mengenai batas usia perkawinan dengan menggunakan pendekatan antropologi. dengan meninjau keputusan hakim dalam kasus dispensasi perkawinan yang berfokus pada kecenderungan usia pengantin untuk melihat usia minimum untuk memiliki dispensasi perkawinan di setiap wilayah. Penelitian menunjukkan bahwa usia terendah untuk mengajukan dispensasi perkawinan di Jawa Tengah adalah 12 tahun 9 bulan untuk perempuan, dan 15 tahun 10 bulan untuk laki-laki. Mayoritas hakim tidak mempertimbangkan usia partai, melainkan alasan dan kondisi dari partai yang mengajukan.